Ferroelectricity Driven by Twisting of Silicate Tetrahedral Chains1. Issue 31 (14th June 2013) - Taniguchi, Hiroki; Kuwabara, Akihide; Kim, Jungeun; Kim, Younghun; Moriwake, Hiroki; Kim, Sungwng; Hoshiyama, Takuya; Koyama, Tsukasa; Mori, Shigeo; Takata, Masaki; Hosono, Hideo; Inaguma, Yoshiyuki; et al.
<x xml:space="preserve">Abstract</x> A lead‐free ferroelectric: The occurrence of ferroelectricity is demonstrated in a silicate‐based compound (Bi2SiO5, see picture), by direct observation of polarization switching. The mechanism of ferroelectricity in Bi2SiO5 has been studied by Raman scattering, transmission electron microscopy, X‐ray powder diffraction, and first‐principles calculations. The observed ferroelectricity stems from twisting of the one‐dimensional SiO4 tetrahedral chain.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>